Characterization of Developmental Changes in Spontaneous Electrical Activity of Medial Superior Olivary Neurons Before Hearing Onset With a Combination of Injectable and Volatile Anesthesia - Di Guilmi, Mariano Nicolás; Rodríguez-Contreras, Adrián (Frontiers in Neuroscience, 2021)
In this work the impact of two widely used anesthetics on the electrical activity of auditory brainstem neurons was studied during postnatal development. Spontaneous electrical activity in neonate rats of either sex was analyzed through a ventral craniotomy in mechanically ventilated pups to carry out patch clamp and multi-electrode electrophysiology recordings in the medial region of the superior olivary complex (SOC) between birth (postnatal day 0, P0) and P12. Recordings were obtained in pups anesthetized with the injectable mix of ketamine/xylazine (K/X mix), with the volatile anesthetic isoflurane (ISO), or in pups anesthetized with K/X mix that were also exposed to ISO. The results of patch clamp recordings demonstrate for the first time that olivary and periolivary neurons in the medial region of the SOC fire bursts of action potentials. The results of multielectrode recordings suggest that the firing pattern of single units recorded in K/X mix is similar to that recorded in ISO anesthetized rat pups. Taken together, the results of this study provide a framework to use injectable and volatile anesthetics for future studies to obtain functional information on the activity of medial superior olivary neurons in vivo.